PENGARUH MODAL DAN VOLUME USAHA TERHADAP SISA HASIL USAHA PADA KUD SELIKUR MAKMUR KABUPATEN MUARO JAMBI - Jefri Febrian Putra; Mulia Inda Purwati (JUMANJI (JURNAL MANAJEMEN JAMBI), 2024)
In this research, a study was carried out on the influence of capital and business volume on residual business results. This research aims to determine the effect of capital and business volume on the remaining business results at KUD Selikur Makmur in Bukit Jaya Village, Kec. South Bahar, Kab. Muaro Jambi. This research uses a quantitative approach using secondary data from 2023 with 41 samples obtained from where the research took place. The analysis technique used is multiple regression analysis with the IBM SPSS 29 program. The results of this research show that simultaneously the capital and business volume variables have a significant effect together on the remaining business results in KUD Selikur Makmur Bukit Jaya Village, Kec. South Bahar, Kab. Muaro Jambi. Keywords: Capital, Business Volume, SHU KUD Selikur Makmur.